Gender Differences on SF-36 Patient-Reported Outcomes of Diabetic Foot Disease. (June 2018) - Del Core, Michael A.; Ahn, Junho; Wukich, Dane K.; Liu, George T.; Lalli, Trapper; VanPelt, Michael D.; Raspovic, Katherine M.
The primary aim of this study was to evaluate the impact of gender on health-related quality of life (HRQOL) using a generic (Short Form–36 [SF-36]) and region-specific (Foot and Ankle Ability Measure [FAAM]) health measurement tool among a matched cohort of male and female patients with diabetes-related foot complications. The HRQOL of 240 patients with diabetic foot disease was measured using the SF-36 and the FAAM surveys. A total of 120 male patients were matched with 120 female patients with the same primary diagnosis, age, type, and duration of diabetes and insulin use. The SF-36 physical component summary (PCS) and mental component summary (MCS) scores were calculated using orthogonal and oblique rotation methods. The median age of the respondents was 54 years (interquartile range = 46-61). No differences in patient characteristics were found between genders. Among the SF-36 subscales, women reported significantly worse physical function ( P = .014) and bodily pain ( P = .021) scores with a trending decrease in general health score ( P = .067). Subsequently, women had worse orthogonal ( P = .009) and oblique PCS scores ( P = .036) than men. However, orthogonal ( P = .427) or oblique ( P = .140) MCS scores did not differ between groups. No significant differences in FAAM scores with respect to gender were appreciated. Our findings suggest that in patients with diabetic foot disease, women tend to report lower physical HRQOL compared with men. In efforts to increase compliance, providers should recognize the impact of gender on patients' perceptions of foot-related complications of diabetes. This knowledge may improve outcomes by adapting more individualized and gender-specific approaches to patients.